Teachers’ Acceptance of Using Digital Technology in Teaching English - Alfian, Ahmad; Noni, Nurdin; Sofyan, Ryan Rayhana (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study investigates the acceptance and use of digital technology in English language teaching by teachers at SMA Negeri 2 Jeneponto. It focuses on their attitudes, the digital tools they implement, and the challenges they face. Using a qualitative research approach, data were collected through classroom observations and interviews with English teachers. The results show that most teachers hold a positive attitude toward the use of digital technology, recognizing its benefits in improving student engagement and enhancing learning outcomes. Teachers utilize various digital tools such as Smart TVs, LCD projectors, educational applications, and online platforms to create more interactive and flexible learning environments. However, despite this positive outlook, several obstacles hinder the effective integration of technology into the classroom. These challenges include limited access to reliable technical resources, insufficient institutional support, and varying levels of digital literacy among both teachers and students. To address these issues, the study suggests enhancing technological infrastructure, offering ongoing professional development programs, and establishing clear guidelines for the use of technology in teaching. These recommendations aim to support the successful adoption of digital tools in English instruction. Additionally, future studies are encouraged to examine the long-term effects of digital technology on students’ language proficiency and evaluate effective training models for teachers.